Preparation and catalytic performance of Pt/double helix polyaniline nanocomposites. Issue 4 (1st October 2020) - Li, Linxiu; Xu, Xuecheng
ABSTRACT: In this study, we design and synthesize double helix hollow nanotube polyaniline (DHPANI) using C18 -L glutamic acid as a template. Then, DHPANI is acted as the substrate, and Pt@DHPANI nanocomposites are well prepared by using potassium chloroplatinate as the Pt source and formaldehyde as the reducing agent through adsorption reduction. Characterization results indicate that Pt@DHPANI nanocomposites have excellent and stable double helix morphology, and the hollow diameter is about 20 nm, which greatly increases the specific surface area of the polyaniline. Moreover, Pt nanoparticles (NPs) with an average particle size of about 50 nm are distributed on the surface of nanocomposites. Furthermore, it is found that the interaction between Pt NPs and DHPANI greatly increases, which makes the electron delocalization enhanced, causing more difficult for Pt NPs to lose/release electrons. In the catalytic reduction process of 4-NP, the catalytic efficiency of Pt@DHPANI nanocomposites is twice as much as Pt@PANI nanocomposites, showing excellent and stable catalytic performance.